Klebsiella Lytic Phages Induce Pseudomonas aeruginosa PAO1 Biofilm Formation - Grzegorz Guła; Grazyna Majkowska-Skrobek; Anna Misterkiewicz; Weronika Salwińska; Tomasz Piasecki; Zuzanna Drulis-Kawa (Viruses)
Bacterial biofilms, characterized by complex structures, molecular communication, adaptability to environmental changes, insensitivity to chemicals, and immune response, pose a big problem both in clinics and in everyday life. The increasing bacterial resistance to antibiotics also led to the exploration of lytic bacteriophages as alternatives. Nevertheless, bacteria have co-evolved with phages, developing effective antiviral strategies, notably modification or masking phage receptors as the first line of defense mechanism. This study investigates viral–host interactions between non-host-specific phages and Pseudomonas aeruginosa, assessing whether bacteria can detect phage particles and initiate protective mechanisms. Using real-time biofilm monitoring via impedance and optical density techniques, we monitored the phage effects on biofilm and planktonic populations. Three Klebsiella phages, Slopekvirus KP15, Drulisvirus KP34, and Webervirus KP36, were tested against the P. aeruginosa PAO1 population, as well as Pseudomonas Pbunavirus KTN6. The results indicated that Klebsiella phages (non-specific to P. aeruginosa), particularly podovirus KP34, accelerated biofilm formation without affecting planktonic cultures. Our hypothesis suggests that bacteria sense phage virions, regardless of specificity, triggering biofilm matrix formation to block potential phage adsorption and infection. Nevertheless, further research is needed to understand the ecological and evolutionary dynamics between phages and bacteria, which is crucial for developing novel antibiofilm therapies.